"ADA Library Heydər Əliyev 100" Book Fair Photo Album - ADA University Library (ADA University, 2023)
Photo album from the International Book, Science and Culture holiday dedicated to the 100th anniversary of National Leader Heydar Aliyev.
Keywords: ADA University -- Book fair.; ADA University -- Aliyev, Heydar -- Centennial.; ADA University -- Aliyev, Heydar -- Book fair -- Photo album.